Geochemistry and petrogenesis of extension-related magmas close to the volcanic front of the Central part of the trans-mexican volcanic belt - Verma, Surendra P.; Torres Sánchez, Darío; Velasco Tapia, Fernando; Subramanyam, K.S.V.; Manikyamba, Chakravadhanula; Bhutani, R. (Dr. James Kellog, 2016)
New geochemical data for 23 samples from the Sierra de Chichinautzin (SCN) and Sierra Santa Catarina (SSC) located at the volcanic front of the central part of the Trans-Mexican Volcanic Belt were combined with the published data on 580 samples from the SCN to explore the origin and evolution of the Qua- ternary trachybasalt and basalt to andesite and dacite. The rare-earth element concentrations for the evolved intermediate and acid rocks are lower than those for the more basic varieties, implying that the evolved magmas cannot be generated by a simple fractional crystallisation process without crustal assimilation. The size of the Nb and Ta negative anomalies increases from basic to acid, which is similar to the behaviour of most continental rifts and extension-related areas, but contrasts from all island and continental arcs. The multidimensional tectonomagmatic diagrams indicate a continental rift setting from basic and alkaline intermediate magmas. The SSC represents a new site of within-plate alkaline magmas discovered in this work, which complements the earlier interpretation of the adjacent SCN as a manifestation of continental rift or extension-related magmatism.